Hazard assessment for a pharmaceutical mixture detected in the upper Tennessee River using Daphnia magna - D. Wolfe; M. Schorr; M. Hanson; C.H. Nelson; S.M. Richards (Global Journal of Environmental Science and Management)
Widespread use of pharmaceuticals has resulted in mixture concentrations ranging from mg/L in effluent to µg/L concentrations in surface water. In a 2008 study, 13 pharmaceuticals, ranging in amounts from 0.0028 to 0.1757 µg/l, were identified in the Tennessee River, USA and its tributaries. In order to address the need for risk assessment of environmentally relevant pharmaceutical mixtures, Daphnia magna 21-d life cycle tests were performed on a mixture of 11 of the 13 pharmaceuticals as well as on the individual components of the mixture. Mixture exposures were based on the same initial ratios of individual compounds, up to 1000x the initial mixture concentrations.  The endpoints of mortality, time to first brood, size, and fecundity were the assessed.  The LOEC of the 11- pharmaceutical mixture was determined to be 100x greater than the measured mixture concentration detected in the Tennessee River, with the NOEC being 75x that of the measured mixture.  Single concentrations of pharmaceuticals within the mixture up to the 100x LOEC were not statistically different from control for any of the assessed endpoints.  Thus, no single pharmaceutical was deemed predominately responsible for the mixture toxicity at the concentrations tested. While mixtures of pharmaceuticals are common in many systems, based on the findings of the present study, they may not pose a significant acute or chronic hazard to aquatic invertebrates at current concentrations.